Factors influencing early childhood development learners’ langauage literacy development: Teachers’ perspective in Zvishavane District - Mutandagai, Esnath Virginia; Manzunzu, Nomatter; Maera, Joyce (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The research study focused on exploring factors influencing ECD learners’ language literacy development from the teachers’ perspective in Zvishavane district. The research study used interpretive paradigm because it believes everything is based on experience. Six ECD teachers of these two were Teachers- in- charge were purposively sampled. Data were generated using interviews and observation. Data were presented in narratives and analysed in themes. Findings from the research indicated that all the respondents gained knowledge on ECD learners’ literacy development through immense training. The perspectives of teachers vary among individuals, however, views expressed by the participants had a connotation of negativity and lack of provisions for the implementation of literacy tasks to ECD learners. It was also observed and confirmed that all visited schools lack provisions such as textbooks and infrastructure that is meant to develop ECD learners’ literacy development. The only observable provisions in visited classrooms were wall charts, reading cards and improvised libraries which as a result inspire boredom to ECD learners since there is nothing interesting to them. The study concludes that there is a great influence on environmental factors since they impel literacy development in ECD learners. The research recommends further studies on literacy development with ECD learners in a different town or community as this might not be affecting one district only.  The research study can redirect teachers to approach literacy development in a more positive and robust way.